Mastery of Kanji Character Meanings through Visual Image Methods among Japanese Language Learners in North Sumatra - Hasanah, Khairunnisa Nur; Febrianti, Dea Nadilla; Syah, Tengku Cinta Zanice; Simanjuntak, Desyca Putri Tiara; Taulia; Yusuf, Muhammad (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2024)
This study aims to investigate the difficulties Japanese language learners face in understanding and mastering the meanings of kanji characters, as well as to evaluate the effectiveness of the image-based visual method in helping learners comprehend and master kanji. A qualitative approach with a descriptive method was employed in this study. The data were collected through pre-tests and post-tests administered to 12 Japanese language learners at Universitas Harapan Medan. The results indicate that prior to the image-based visual learning method, students encountered difficulties in mastering the meanings of kanji characters. The pre-test scores revealed challenges in recalling the meanings of kanji, the correct order of strokes, and the pronunciation associated with kanji. However, after the implementation of the image-based visual learning method, there was a significant improvement in the post-test scores. The average score increased from 37.92 in the pre-test to 80.42 in the post-test. Based on these findings, it can be concluded that Japanese language learners struggle to master kanji meanings. However, the image-based visual learning method proved effective in helping them understand and master kanji, with significant improvements observed. This learning method helped learners recall and understand kanji characters and overcome the difficulties they faced previously.